A Study on the Effectiveness of the Services of Mobile Banking as Perceived by Students of Pamantasan ng Lungsod ng Maynila - Ortiz, Jane Claire C., Regio, Shane Kian B., San Pedro, Louisse Angelica S., Valentino, Ma. Shekainah Adonica M., Villanueva, Mikka A., Violeta, Pola Marie R. 4 0 16; 5 (2023)
Mobile banking has been around since the 1990s and has significantly impacted the banking industry. This study examines the effectiveness of mobile banking in the Philippines, specifically for PLM students. The research aims to identify the key factors-service quality, and convenience-that influence the effectiveness of mobile banking services. Moreover, the study involved 114 respondents, who were 3rd year Financial Management students, selected through a convenience sampling method. The researchers utilized Google Forms as a platform to conduct surveys, reaching out to students through posters and online channels to gather responses. The findings indicate that mobile banking services are highly effective, with an overall weighted mean score of 3.55. The majority of mobile banking users fall within the 21-22 age bracket, and females tend to use the application more often than the males. The paper concludes that the usage of the factors listed in the article to assess each factor's performance will benefit the financial sector, and more specifically the mobile banking sector. The study recommends that the mobile banking industry should enhance their application by expanding the range of services provided to increase the competitiveness in modern technology. Overall, this research sheds light on the factors influencing the effectiveness of mobile banking services for PLM students, highlighting areas for improvement and emphasizing the importance of variety of the service offerings in maintaining a competitive edge in the financial industry. Keywords: mobile banking, effectiveness, service quality, convenience.
Research Paper: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2023.
Keywords: 2 -- 0; 6; 20; 20; 2